Recent Advances in Understanding the Reversal of Gene Silencing During X Chromosome Reactivation - Talon, Irene; Janiszewski, Adrian; Chappell, Joel; Vanheer, Lotte; Pasque, Vincent (Frontiers in Cell and Developmental Biology, 2019)
Dosage compensation between XX female and XY male cells is achieved by a process known as X chromosome inactivation (XCI) in mammals. XCI is initiated early during development in female cells and is subsequently stably maintained in most somatic cells. Despite its stability, the robust transcriptional silencing of XCI is reversible, in the embryo and also in a number of reprogramming settings. Although XCI has been intensively studied, the dynamics, factors and mechanisms of X chromosome reactivation (XCR) remain largely unknown. In this review, we discuss how new sequencing technologies and reprogramming approaches have enabled recent advances that revealed the timing of transcriptional activation during XCR. We also discuss the factors and chromatin features that might be important to understand the dynamics and mechanisms of the erasure of transcriptional gene silencing on the inactive X chromosome (Xi).